Some studies on elemental and isotopic analysis by spectrometry of coincident nuclear reactions products - Coetzee, P. P.(Paulus Philippus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- Universiteit van Stellenbosch, 1974.